The crystal structure of (4-nitrophenyl) (5-ferrocenyl-3-(trifluoromethyl)-1H-pyrazol-1-yl) methanone, C21H12F3FeN3O3 - Guo Ying; Ruan Ban-Feng (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C21H14F3FeN3O3, triclinic, P1̄ (no. 2), a = 7.961(3) Å, b = 11.136(4) Å, c = 11.588(4) Å, α = 76.357(10)°, β = 84.998(10)°, γ = 76.989(10)° V = 972.1(6) Å3, Z = 2, Rgt(F) = 0.0509, wRref(F2) = 0.1304, T = 273(2) K.